Reactivity of the saturated, aromatic, and resin fractions of ATR resids under FCC conditions - Pujro Tarquino, Richard Alfonzo (2013)
SARA (saturate, aromatic, resin and asphaltene) fractions composing an atmospheric tower resid from a naphthenic crude were separated using the ASTM 2007 method. Two commercial equilibrium catalysts, of the conventional and resid types, were used to convert the aromatic, resin and saturate fractions under conditions of the FCC process. The reaction experiments were performed in a CREC Riser Simulator reactor. Reaction temperature was 550 °C, reaction times were from 5 to 20 s, the catalyst mass was 0.8 g and the catalyst to oil relationship was 5.0. The various fractions were used dissolved in toluene at 20 wt.%. The hydrocarbon reaction products were grouped into dry gas, LPG, compounds in the gasoline and LCO boiling ranges and coke. All the fractions converted almost completely, but differences in the yields of the main hydrocarbon groups were observed which revealed the fractions’ nature.